Liquid fear - Bauman, Zygmunt (Polity Press, 2006)
Modernity was supposed to be the period in human history when the fears that pervaded social life in the past could be left behind and human beings could at last take control of their lives and tame the uncontrolled forces of the social and natural worlds. And yet, at the dawn of the twenty-first century, we live again in a time of fear. Whether its the fear of natural disasters, the fear of environmental catastrophes or the fear of indiscriminate terrorist attacks, we live today in a state of constant anxiety about the dangers that could strike unannounced and at any moment. Fear is the name we give to our uncertainty in the face of the dangers that characterize our liquid modern age, to our ignorance of what the threat is and our incapacity to determine what can and can't be done to counter it. This new book by Zygmunt Bauman one of the foremost social thinkers of our time is an inventory of liquid modern fears. It is also an attempt to uncover their common sources, to analyse the obstacles that pile up on the road to their discovery and to examine the ways of putting them out of action or rendering them harmless. Through his brilliant account of the fears and anxieties that weigh on us today, Bauman alerts us to the scale of the task which we shall have to confront through most of the current century if we wish our fellow humans to emerge at its end feeling more secure and self-confident than we feel at its beginning.